Penggunaan Model Regresi Logistic Untuk Menguji Faktor-Faktor Yang Mempengaruhi Penerimaan Going Concern Audit Opinion Pada Industru Perbankan - Astuti, Dewi Saptantinah Puji; Sarwono, Aris Eddy (Graduasi: Jurnal Bisnis & Ekonomi, 2015)
A going concern assumption survival in an entitys financial reporting, so that if an  entity  has  a  condition  that  otherwise  it  shall  become  problematic.  The  main problems  in  the  banking  sector  in  Indonesia  is  like  the  crisis  in  1999.  The  main objective of this study was to determine the main factors that affect the acceptance of a going concern audit of the banking industry in Indonesia. The data used in this research is  data  from  the  financial  statements  of banks  in  2011  to  2013 by purposive sampling technique sampling.Technik retrieval of data using the technique documentation of the data  in  the  IDX  (Indonesia  Stock  Exchange),  especially  for  the  banking  sector  in Indonesia. Testing hypothesis  in  this  study  using  multivariate  analysis  using  logistic regression (logistic-regresion), results showed that audit tenure, the quality of audit and independent  commissioners  have  influence  on  giving  opinions  going  concern,  but shopping opinion, independent directors and managerial ownership has no effect to the going concern opinion